From the Baba’id Rebellion to Ghizilbash Status - Yashar Ahmad Ajagh; Shihab Vali (تاریخ اسلام)
The history of ‘Alawite inclinations in Anatolia and the quality of the penetration of Shi‘ah thought into their belief system has been largely ignored by researchers throughout history. In fact, the roots of ‘Alawite beliefs can be traced back to ancient times from when Turkic tribes resided in Transoxiana to their migration to Anatolia. Gradually, this pattern of life resulted in an eclectic theology that has borrowed a thing or two from every geographical area they passed through and every religion they encountered. What is certain is that Shi‘i opinions influenced the ‘Alawite belief system mostly through the Hurufiyah Order and missionary work by Safavid sheikhs in Anatolia in the 15th and 16th centuries CE, changing the ‘Alawites of Ottoman Anatolia into the Ghizilbash of Safavid Iran.